Control curiosity issues maintaining consumers active on sustainability - Gunawan, Lieptiono; Prayitno, Prayitno (Central Research Institute for Agriculture (CeRIA), 2024)
Active consumers play a dual role in one marketing chain, their existence as consumers and as passive marketers outside the company. Dependence on the latest products released by the company arouses consumers' great curiosity so that they automatically look for information about the latest products that will be released and form a community. This research uses a qualitative descriptive method with an inductive approach , using a conceptual theory model, and a constant comparison method. The research results of the concept of novelty integrate theory and explain the concept of novelty in detail as well as the formation of an active consumer process.